Pengembangan Perangkat Pembelajaran Matematika Berbasis SBL Untuk Meningkatkan Kemampuan Pemecahan Masalah Peserta Didik Kelas VIII - yerizon yerizon; Debby Marinda (Universitas Islam Sultan Agung, 2021)
The problems found in the field were the low ability of students to solve problems, the preparation of mathematics learning tools that were still not in accordance with the characteristics of students. For this reason, a research development of mathematics learning tools has been designed. The purpose of this study was to describe the process and results of developing Situation Based Learning (SBL) based mathematics learning tools to improve the valid, practical and effective problem solving abilities of class VIII students. This type of research is development research, using Plomp's research procedures, namely the preliminary research phase, the development or prototyping phase and the assessment phase. This device was tested in SMP 06 Padang by taking three students for one to one (class VIII.1) and six students for the small group (VIII.3). The results of this study indicate that the device developed is valid with an average score of 0.862 for lesson plans and 0.965 for student worksheets, practical with an average score of 91.92% practicality and effective with a mastery of material completeness of 82.89%.